ASSESSMENT OF PHYTOCHEMICAL DIFFERENCES BETWEEN TWO COCOYAM VARIETIES GROWN IN PORT HARCOURT - Ekpenyong , Bassey Okon; Ndoma , Esther Ijeoma (Ayden International Journal of Basic and Applied Sciences, 2025)
The transfusion transmitted Cytomegalovirus (TTCMV) may complicate the frequent pRBC transfusion in βthalassemia major (Choobineh et al., 2009). The possibility of CMV transmission in these patients was looked up as the units of blood were neither screened for this infection nor leukoreduced. The aim of this study was to detect the seroprevalence of CMV infection in transfusion dependent thalassemia patients and its relation with the molecular study. A total of 123 children and adolescent; 50 normal and 73 were patients with β-TM on regular blood transfusion. A blood sample was taken from each individual, controls and pre-transfusion patients, and submitted to serological (ECLIA) and molecular (real tine PCR) study. The prevalence of CMV IgG specific antibody was 100% in both patients and control while no one of them showed reaction to CMV IgM specific antibody. The CMV IgG avidity index was high in all β-TM patients except for one patient (1.3%) showed low IgG avidity index, while all the control individuals (100%) have had high IgG avidity index. The viral DNA was not detected in the peripheral blood of the entire study sample detection